2016
DOI: 10.1002/adfm.201504201
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Spin Injection and Spin Transport in Organic Spin Valves Using π‐Conjugated Polymer Brushes

Abstract: Charge transport in amorphous organic semiconductors is governed by carriers hopping between localized states with small spin diffusion length. Furthermore, the interfacial resistance of organic spin valves (OSVs) is poorly controlled resulting in controversial reports of the magnetoresistance (MR) response. Here, surface‐initiated Kumada transfer polycondensation is used to covalently graft π‐conjugated poly(3‐methylthiophene) brushes from the La0.67Sr0.33MnO3 (LSMO) bottom electrode. The covalent attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…Because the epitaxial growth technology of organic materials on metal surfaces is not available for OSCs thus far, a possible way to control the interface is to chemically grow a self‐assembled monolayer (SAM) on the magnetic electrodes. This type of SAM controlled spinterface effect in π‐conjugated polymer brushes based OSVs has recently been achieved by Geng et al…”
Section: Discussionmentioning
confidence: 90%
“…Because the epitaxial growth technology of organic materials on metal surfaces is not available for OSCs thus far, a possible way to control the interface is to chemically grow a self‐assembled monolayer (SAM) on the magnetic electrodes. This type of SAM controlled spinterface effect in π‐conjugated polymer brushes based OSVs has recently been achieved by Geng et al…”
Section: Discussionmentioning
confidence: 90%
“…The performances of this type of devices have been compared with those of a similar one obtained by replacing the double decker layer with diamagnetic molecules, the diethyl(11‐iodoundecyl)phosphonate, bearing the same linking group promoting the chemisorption. This strategy has been developed in order to disentangle the effect of the chemical functionalization of the manganite, which has been addressed also in earlier reports, from more specific effects, due to the presence of a layer of magnetic molecules forming an additional spinterface for the spin injection into the OSC.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier experimental studies have shown that the spins in ferromagnetic nanoparticles can interact with nearby orbital fields in organic molecules, generating spin–orbital interactions at the ferromagnetic/organic interface . Furthermore, using the ferromagnetic surface represents the most direct approach to inject spins into semiconductors, leading to a spin‐selective interface . In general, the spin‐selective interface requires the direct contact between a ferromagnet and an organic semiconductor by overlapping their orbital wave functions.…”
mentioning
confidence: 99%